Recepcja teorii ludności T. R. Malthusa w polskiej myśli społecznej na przełomie XIX i XX w. - Bołdyrew, Aneta (Studia z Historii Społeczno-Gospodarczej XIX i XX Wieku, 2009)
In Polish social and economic discussion of the problems of population there were more opponents than advocates of the Malthus’s law. By criticizing the theory the opponents found the point of reference for their own principles. The publicists and scholars representing various circles and philosophies of life emphasized the need to standardize the level of fertility. They did not agree with the idea that the process of reproduction of population does not need to be connected with limitation of birth-rate. L. Krzywicki and Z. Daszyńska-Golińska who sympathized with socialistic tendencies did not agree with Malthus’s recommendation of sexual restraint. They thought that only social reforms and the improvement of conditions of living of the working class can influence their procreation activity. The publicists connected with Catholic church claimed that the creation of the law of population of neo-malthusianism is one of the consequences of theory of the English economist which, in their view, discredited its value. The economists who distanced from socialistic ideas frequently agreed with numerous theses of the law of population. One of them was the advocate of economic liberalism A. Krzyżanowski. The polemics on theory of population by Malthus in Polish, as well as in European commentary expanded the discussion and the exchange of opinions on social and economic relations. It also drew attention to the necessity of formulation of population politics. Many scholars who in their journals on the turn of XIXth century paid attention to the themes of population and who analysed the idea through the prism of Malhus’s theory used the experiences in the second Reich and included the demographic ideas to political programs of social and economic reconstruction of Poland.